Progressive Confirmation of Two Mental Systems - López Astorga, Miguel (Problemos, 2024)
From current cognitive science, some theories propose that the human mind includes two systems: a system leading quick intuitions and a system ruling slow logical reasoning. Given that the systems are in the mind, one might think that their existence is difficult to check. This paper presents a way to gradually confirm the hypothesis about the two systems. It adopts the conception of the two systems as presented by the theory of mental models. Moreover, following Carnap’s proposal of reduction, the paper describes two procedures to incrementally confirm the hypothesis. One of them investigates human performance at inferences in the form of Modus Tollendo Tollens. The other one investigates inferences from an exclusive disjunction having three disjuncts.